2008
DOI: 10.1128/jvi.02324-07
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Hypovirus-Derived Small RNAs Generated in the Chestnut Blight Fungus by an Inducible DCL-2-Dependent Pathway

Abstract: The disruption of one of two dicer genes, dcl-2, of the chestnut blight fungus Cryphonectria parasitica was recently shown to increase susceptibility to mycovirus infection (G. C. Segers, X. Zhang, F. Deng, Q. Sun, and D. L. Nuss, Proc. Natl. Acad. Sci. USA 104:12902-12906, 2007). We now report the accumulation of virusderived small RNAs (vsRNAs) in hypovirus CHV1-EP713-infected wild-type and dicer gene dcl-1 mutant C. parasitica strains but not in hypovirus-infected dcl-2 mutant and dcl-1 dcl-2 double-mutant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
100
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(110 citation statements)
references
References 72 publications
10
100
0
Order By: Relevance
“…In facts, as already shown by the results obtained with different techniques using exactly the same RNA sample as template, in the isolate MUT4330, the majority of viruses are detectable with the sRNA technique but one, the PaBv1, seems to be able to escape almost completely the quelling machinery since only for this virus, the number of sequenced sRNA was minimal ( Table 2). Accumulation of vsRNA is characteristic of RNA silencing-based antiviral defense, but in case of dicer-like or argonaute mutants the accumulation of this vsRNA is greatly affected (Segers et al, 2007;Zhang et al, 2008). Moreover some fungi have completely lost the genes for the RNA silencing machinery but do not seem to suffer high incidence of virus-induced symptoms suggesting the possibility of additional and yet uncharacterized mechanism used by fungi to mitigate viral replication (Nakayashiki and Nguyen, 2008).…”
Section: New Tools For Searching and Assembling Mycovirus Genomes: Sumentioning
confidence: 99%
“…In facts, as already shown by the results obtained with different techniques using exactly the same RNA sample as template, in the isolate MUT4330, the majority of viruses are detectable with the sRNA technique but one, the PaBv1, seems to be able to escape almost completely the quelling machinery since only for this virus, the number of sequenced sRNA was minimal ( Table 2). Accumulation of vsRNA is characteristic of RNA silencing-based antiviral defense, but in case of dicer-like or argonaute mutants the accumulation of this vsRNA is greatly affected (Segers et al, 2007;Zhang et al, 2008). Moreover some fungi have completely lost the genes for the RNA silencing machinery but do not seem to suffer high incidence of virus-induced symptoms suggesting the possibility of additional and yet uncharacterized mechanism used by fungi to mitigate viral replication (Nakayashiki and Nguyen, 2008).…”
Section: New Tools For Searching and Assembling Mycovirus Genomes: Sumentioning
confidence: 99%
“…In this antiviral defense, small interfering RNAs (siRNAs) are processed from a viral RNA precursor and used to guide specific silencing of the cognate viral RNAs in an Argonaute-containing effector complex. In fruit flies, nematodes, and fungi, doublestranded RNA (dsRNA) replicative intermediates of viral RNA genomes are recognized and processed into virus-derived siRNAs by a single host Dicer (Schott et al, 2005;Wilkins et al, 2005;Galiana-Arnoux et al, 2006;Wang et al, 2006;Aliyari et al, 2008;Zhang et al, 2008;Lu et al, 2009;Wu et al, 2010). However, production of viral siRNAs in plants involves multiple Dicer-like proteins (DCLs) (Blevins et al, 2006;Bouché et al, 2006;Deleris et al, 2006;Fusaro et al, 2006;Moissiard and Voinnet, 2006;Diaz-Pendon et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…We subsequently showed that dcl-2 functions to process mycovirus RNAs into virus-derived small interfering RNAs (vsRNAs) as part of an inducible RNA silencing antiviral response (15). Cloning and characterization of vsRNAs generated from hypovirus CHV1-EP713 revealed a nonrandom distribution of vsRNAs along the 12.7-kb genome RNA.…”
mentioning
confidence: 99%
“…Cloning and characterization of vsRNAs generated from hypovirus CHV1-EP713 revealed a nonrandom distribution of vsRNAs along the 12.7-kb genome RNA. Conspicuous was the very low representation of vsRNA mapping to an internal portion of the 12.7-kb genome RNA that encodes the viral polymerase and helicase domains, from map position 7500 to 11000 (15). It has been postulated that the propensity of hypoviruses to generate internally deleted DI RNAs results in a lower level of substrate for vsRNA biogenesis from this region (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation